Groundwater quality assessment using groundwater pollution index (PIG) and non-carcinogenic human health risk assessment of fluoride and nitrate (HHR) in a semi-arid region of Mascara (northwestern of Algeria) - Benamina, Benyelkhlef; Bentabet, Abdelkader; Azzaz, Habib; Dahmani, Ali; Hamimed, Abderrahmane (Brawijaya University, 2025)
This article discusses nitrate and fluoride contamination and potential health risks for men, women, and children in the Mascara region (northwestern Algeria). To achieve this objective, the Groundwater Pollution Index (PIG) was used to assess the health risks caused by fluoride and nitrates in water. The concentration of nitrate varied, between 2 and 144 mg/L, was observed, with 44% of samples exceeding the WHO permitted limit of 50 mg/L. The study revealed that groundwater with high F concentration is found in evaporite formation as well as cultivated soils. In the studied points, fluoride concentrations range from 0.06 to 3.06 mg/L, with 11% of groundwater exceeding the fluoride guidelines (1.5 mg/L). However, 52%, 58%, and 61% of the region's waters are considered to be at high risk for men, women, and children, respectively, according to the distribution of HQNO3 risk quotient values. The HQF values ??were highest for children (an average of 0.60) and women (an average of 0.52), followed by the lowest values ??for men (an average of 0.45. HHRA results show that 69% of the region's water is considered to pose a high risk for men and women and 78% children respectively. It was observed that nitrate levels have a greater impact on the waters of the region. The calculated PIG values ??range from 0.35 to 1.15, which classifies 95% of the current study area in the insignificant pollution zone (PIG: < 1.0), and the rest (5%) in the low pollution zone (PIG: 1.0 to 1.5).